Diameter of the Cochlear Nerve Canal predicts Cochlear Nerve Deficiency in Children with Sensorineural Hearing Loss - Sorge, Martin; Sorge, Ina; Pirlich, Markus; Fuchs, Michael; Meuret, Sylvia; Hirsch, Franz Wolfgang; Dietz, Andreas; Gräfe, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Purpose Detection of cochlear nerve deficiency (CND) is usually straightforward using magnetic resonance imaging (MRI). In patients in whom MRI cannot be performed or imaging provides equivocal findings, computed tomography (CT) of the temporal bone might offer indirect evidence of CND. Our study aimed to derive a cut-off value for the diameter of the cochlear nerve canal (CNC) and internal auditory canal (IAC) in temporal bone CT to predict CND.Materials and Methods This retrospective study included 70 children with sensorineural hearing loss (32 with CND and 38 control patients). The height, width, and cross-sectional area of the IAC and diameter of the CNCs were determined using temporal bone CT. Receiver operating characteristic (ROC) and Student’s t-tests were performed for each parameter.Results The mean diameter of the CNCs was significantly smaller in children with CND than in the control group (1.2 mm versus 2.4 mm, p < .001). The optimal threshold for CNC for separation of the two groups was 1.9 mm, resulting in a sensitivity of 98.7 % and specificity of 89.2 %. The IAC dimensions could not distinguish between children with CND and controls.Conclusion A CNC diameter of less than 1.9 mm is a reliable predictor of CND in children with sensorineural hearing loss.Key Points: Citation Format
Keywords: internal auditory canal; cochlear implantation; cochlear nerve dysplasia; cochlear nerve canal